Temephos resistance levels in populations of Aedes aegypti (Diptera: Culicidae) from Havana, Cuba - Luis Augusto Piedra; Yanisley Martínez; Eric Camacho; Israel Garcia; Dayana Rodriguez; María del Carmen Marquetti; Veerle Vanlerberghe (Open Journal of Tropical Medicine - Peertechz Publications, 2023)
Aedes aegypti chemical control remains an indispensable alternative to prevent dengue, Zika, and Chikungunya outbreaks. Havana City requires constant surveillance due to its bioecological characteristics favor the proliferation of mosquito vectors of these diseases, which constitutes a high risk to the health of its inhabitants. The goal of this study was to determine temephos resistance levels in the populations of Ae. aegypti from five municipalities of Havana. The susceptibility of the larvae was evaluated by bioassays described by the World Health Organization. Aedes aegypti populations evaluated showed high resistance to temephos, with values that oscillated for the FR50 between 26,8 and 82,5 and for the FR90 between 16,6 and 42,5 respectively. The National Control Program of Aedes aegypti in Cuba must promote insecticide rotation policies to avoid or prevent the evolution of temephos resistance in Havana. In addition, an evaluation of the Abate doses applied by the operators in the municipalities studied must be carried out, since this could be influencing resistance development due to operational factors.